Caracterização morfoagronômica e diversidade genética em populações F3 de pimenteiras ornamentais (Capsicum annuum L.) - Mesquita, Julio Carlos Polimeni de (2015)
Capsicum genus presents wide genetic variability and the most used way to determine this variability is through morphological descriptors, essential to obtain information on available diversity, making it possible to better use in breeding programs. Knowledge of this diversity is critical for breeding program of the species one wants to improve, which could be, in the case of pepper plant, cultivar development that are intended for fruit production, for fresh consumption, industries: food of condiments, canned and dyes; pharmaceutical; cosmetics; for use as a rootstock, or more recently as ornamental plant. So the first chapter of this doctoral thesis aimed to characterize and evaluate genetic divergence and heritability of morphoagronomic characteristics in thirteen populations of ornamental pepper plant, being eight populations F3: F21 (P-1), F24 (P-2), F25 (P-3), F27 (P-4), F29 (P-5), F210 (P-6), F211 (P-7) and F231 (P-8), of crossing between the accesses 134 (P-9) and 77.2 (P10), and five additional witnesses: accesses 134 (P9), 77.2 (P10), 10.1 (P11), 10.2 (P-12), and 10.3 (P-13). The P-9 access presents small size, green leaves, white flowers, and cream to red small fruits. The P-10 access is composed of high-sized plants with vein-like leaves, purple flowers and small fruits and lilac to red fruits. P-11, P-12, and P-13 accesses show plants with very similar size characteristics, large and showy fruits, only differing in the color of ripe fruit P-11 (yellow), P-12 (red), and P-13 (orange). The work was conducted in a greenhouse. Fifty plants of each F3 population and ten of each additional witnesses were distributed in a completely randomized experimental design with two factors: Population and Years. Sixteen morphological descriptors were evaluated, being six of plant and ten of fruit. Variance analysis was performed with the data of the five witnesses and used residual mean squared error to conduct the means comparison test. Genotypes were grouped according to Scott-Knott criteria (p ≤ 0.05). The interaction was significant for all traits, except for the height of the first fork and number of seeds per fruit. The heritability ranged from 91.18% (stem diameter) to 99.97% (greater fruit diameter), for the first year of evaluation, and 85.75% (dry matter content) to 99.65% (higher fruit diameter), for the second year. The relation between genetic variation coefficient and environmental variation coefficient presented values higher than 1 for all traits, except for stem diameter, fruit length / diameter ratio and dry matter content. P3 population was the one with the lowest average for plant height and canopy diameter, thus, being the most recommended for selection of ornamental size. In the second chapter, the objective was to evaluate the genetic divergence between thirteen populations of ornamental pepper plants, using multivariate techniques and determine which morphological characteristics contributed more for genetic divergence. Genetic divergence between populations of ornamental pepper plants was determined by clustering analysis and canonical variables. Multivariate analysis revealed that there is interaction between the studied factors (p <0.01). There was agreement between the multivariate techniques used. Fruit characteristics were those that most contributed for genetic divergence, separating the populations P11, P12 and P13 from other populations. These results were repeated in the two years of evaluation. The third chapter aimed to characterize and estimate genetic divergence within pre-established groups of populations F3 of ornamental pepper plants. Eight F3 populations were evaluated in a completely randomized design with two factors (Populations and Years). Quantitative and qualitative descriptors were used. Dissimilarity matrices were estimated between genotypes within the populations, using Gower dissimilarity coefficient. Ggenotypic divergence explained by dissimilarity matrices were analyzed via non-metric multidimensional scaling (nMDS). Internal consistency presented by populations P4, P6, P7, P5, and P8, indicates that the genotypes of these populations present capability for use in future ornamental pepper plant breeding programs. On the other hand, populations P1, P2, and P3 presented the highest visual dispersion, allowing selection, aiming advancement of future generations.